Impacts of plant tafazzin deficiency on differential gene expression - Hayden, Cole; Welti, Ruth; Zoong Lwe, Zolian (My University, 2023)
Tafazzin is a mitochondrial protein characterized in mammals and yeast. Tafazzin remodels the fatty acids of cardiolipin, aiding in the proper function of the electron transport chain. Although the function of tafazzin is known, the mechanisms and pathways that lead to apoptosis under tafazzin deficiency are unknown. Here we use a homolog of tafazzin in the model plant organism Arabidopsis thaliana to test our null hypothesis that gene expression is not dependent on the presence of functional tafazzin. RNA-seq was performed on leaf samples of wild type plants and mutant plants with mutations of varying severity in the gene encoding tafazzin. The sequencing output was analyzed with a selection of bioinformatics tools that includes HISAT2 (aligner), StringTie (assembler), and DESeq2 (differential gene expression identifier). The results indicate genes that are upregulated or downregulated in response to functional tafazzin’s absence.  One outcome of analysis reveals that the genes that demonstrate the most statistically significant differential expression are nearly all downregulated in the mutants with respect to wild type, and many of them are localized to the mitochondria. Of these, the gene at locus AT3G54730 presents one possible direction of further study as it codes a transcription repressor protein. The downregulation of a transcription repressor may be a contributing factor to the phenotype observed under the condition of tafazzin deficiency, as transcripts relating to apoptosis would be repressed under healthy, unmutated cell conditions. One goal of this analysis is to develop a framework for the metabolic engineering of plants to display stronger resilience against environmental stress.
Keywords: Cardiolipin; Tafazzin; RNA-seq; Arabidopsis; Plant stress; USDA NIFA 2019-67032-29071